2010
DOI: 10.1021/ml1000257
|View full text |Cite
|
Sign up to set email alerts
|

Cobicistat (GS-9350): A Potent and Selective Inhibitor of Human CYP3A as a Novel Pharmacoenhancer

Abstract: Cobicistat (3, GS-9350) is a newly discovered, potent, and selective inhibitor of human cytochrome P450 3A (CYP3A) enzymes. In contrast to ritonavir, 3 is devoid of anti-HIV activity and is thus more suitable for use in boosting anti-HIV drugs without risking selection of potential drug-resistant HIV variants. Compound 3 shows reduced liability for drug interactions and may have potential improvements in tolerability over ritonavir. In addition, 3 has high aqueous solubility and can be readily coformulated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
174
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(185 citation statements)
references
References 26 publications
5
174
1
5
Order By: Relevance
“…After extensive structure activity relationship studies with desoxy-ritonavir, cobicistat (Fig. 14C) was identified as a potent, selective, and orally bioavailable inhibitor of CYP3A (Xu et al, 2010).…”
Section: Investigations Of Human Cytochrome P450 Enzymes Withmentioning
confidence: 99%
See 1 more Smart Citation
“…After extensive structure activity relationship studies with desoxy-ritonavir, cobicistat (Fig. 14C) was identified as a potent, selective, and orally bioavailable inhibitor of CYP3A (Xu et al, 2010).…”
Section: Investigations Of Human Cytochrome P450 Enzymes Withmentioning
confidence: 99%
“…Cobicistat is also more selective for CYP3A than ritonavir, with much reduced inhibitory activity toward CYP2D6, CYP2C8, and CYP2C9. In addition, in vitro studies suggest that cobicistat may have a lower potential to cause undesired drug-drug interactions and lipid disorders than ritonavir (Xu et al, 2010).…”
Section: Investigations Of Human Cytochrome P450 Enzymes Withmentioning
confidence: 99%
“…RTV and COBI both serve as mechanism-based inhibitors of CYP3A4 in vivo (43,44); however, RTV is also known to induce the expression of various metabolic enzymes, including CYP3A4, in primary human hepatocytes in vitro (30). Very few studies aimed at investigating the relative effects of COBI as an inducer of metabolic enzyme expression have thus far been conducted, although it has been suggested that the induction potential of COBI is less than that of RTV (45) and that COBI is not expected to induce CYP3A4 expression (46). It was recently suggested that the hepatic uptake of RTV occurs chiefly by passive diffusion (47).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Cobi is a potent inhibitor of CYP3A enzymes, the main metabolizing pathway of this class of antiretrovirals. 11 Like RTV, Cobi inactivates CYP3A in a concentration-and time-dependent fashion, exhibiting a CYP3A inactivation rate of 0.44 min -1 and an inhibition constant of 939 nmol/L in vitro (corresponding values for RTV were 0.23 min -1 and 256 nmol/L). Potent inhibition of CYP3A activity has also been demonstrated with Cobi in a Phase I study in healthy volunteers (n#60).…”
Section: Overview Of Pharmacologymentioning
confidence: 99%
“…However, due to its more selective inhibition of CYP3A, Cobi has a lower potential for off-target drug interactions than the standard boosting agent RTV, and lower likelihood for enzymatic induction. Cobi, unlike RTV, is devoid of anti-HIV activity in vitro, displaying a mean IC 50 of .30 mmol/L in a HIV-1 protease enzymatic assay (vs 0.0006 mmol/L with RTV), a mean half maximal effective concentration (EC 50 ) of .30 mmol/L in a cell-based HIV infection assay (vs 0.0133 mmol/L with RTV), 11 and no activity against primary HIV isolates. 13 Absorption of Cobi is rapid after oral administration, with the maximum plasma concentration (C max ) of the drug being reached within 4 hours (Table 1). 14 As may be expected for a drug that is both a mechanism-based inhibitor of CYP3A and a CYP3A substrate, exposure to Cobi was nonlinear across oral dosages of 50-300 mg/day in healthy volunteers, with exposure increasing more than proportionally with increasing dose (up to 47-fold).…”
Section: Overview Of Pharmacologymentioning
confidence: 99%